2017
DOI: 10.1186/s12864-016-3438-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the molecular responses of a cucumber segment substitution line carrying Pm5.1 and its recurrent parent triggered by powdery mildew by comparative transcriptome profiling

Abstract: BackgroundPowdery mildew (PM) is one of the most severe fungal diseases of cucurbits, but the molecular mechanisms underlying PM resistance in cucumber remain elusive. In this study, we developed a PM resistant segment substitution line SSL508-28 that carried a segment on chromosome five representing the Pm5.1 locus from PM resistant donor Jin5-508 using marker-assisted backcrossing of an elite PM susceptible cucumber inbred line D8.ResultsWhole-genome resequencing of SSL508-28, Jin5-508 and D8 was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 62 publications
2
54
0
Order By: Relevance
“…Cucumber seedlings of D8 and SSSL508-28 were grown in a growth chamber under controlled conditions (65% relative humidity, 28 • C/16 h light and 20 • C/8 h dark). At 21 days (threeleaf stage), homogeneous plants were selected for inoculation by spraying with a P. xanthii conidia (harvested from naturally infected D8 leaves) spore suspension of 1 × 10 6 conidia/mL containing 0.01% Tween-20 or sterile distilled water until runoff (Xu et al, 2017). The leaves sprayed with the sterile water served as mock controls.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Cucumber seedlings of D8 and SSSL508-28 were grown in a growth chamber under controlled conditions (65% relative humidity, 28 • C/16 h light and 20 • C/8 h dark). At 21 days (threeleaf stage), homogeneous plants were selected for inoculation by spraying with a P. xanthii conidia (harvested from naturally infected D8 leaves) spore suspension of 1 × 10 6 conidia/mL containing 0.01% Tween-20 or sterile distilled water until runoff (Xu et al, 2017). The leaves sprayed with the sterile water served as mock controls.…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…The remaining targets either showed no significant change in their expression levels or had similar expression patterns as the corresponding miRNAs. Among the 92 miRNA-mRNA interaction pairs in D8, two were located on the substituted segment (Chr5:16,676,542-23,484,079 bp;Xu et al, 2017) that includes Csa-miR172c-3p and Csa-miR395a-3p. Eight targets of Csa-miR172c-3p that were negatively regulated upon PM inoculation were classified as TFs, namely, two Dofs (Csa1G009790 and Csa1G033250), one TALE (Csa6G426360), one AP2 (Csa2G279250), one LBD (Csa5G219380), one Trihelix (Csa2G350410), one bHLH (Csa1G612950), and one CO-like (Csa7G031530) (Supplementary Table 7).…”
Section: Negatively Regulated Mirna Target Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that CsWRKYs may play crucial roles in the response to various stresses. To further confirm whether CsWRKYs are involved in the response to various stresses, we analysed the comprehensive expression patterns of CsWRKY genes under different abiotic and biotic stresses, including salt, heat, downy mildew (DM, Pseudoperonospora cubensis) and powdery mildew (PM, Podosphaera fusca), based on public transcriptome information [54,60,61] and transcriptomic data that we generated.…”
Section: Expression Patterns Of Cswrkys In Response To Abiotic and Bimentioning
confidence: 99%
“…To explore the potential functions of CsWRKYs in resistance to biotic stresses, we performed a CsWRKY expression analysis of the susceptible and resistant cucumber lines inoculated with PM for 48 h (Fig. 9A) based on published RNA-seq data [61]. Eleven and 12 CsWRKY genes that were differentially expressed were identified in the susceptible and resistant cucumber lines, respectively, compared with the controls.…”
Section: Expression Patterns Of Cswrkys In Response To Abiotic and Bimentioning
confidence: 99%